Psikologi Perkembangan Membongkar Dan Menjawab Problematik Kehidupan Manusia Mulai Dari Balita - Dewasa - Kemryati Juleha Siburian; Rona Napitupulu; Dorlan Naibaho; Eka Hutagalung (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
Humans are the most complex creatures among all of God's creations in the world. Therefore, every physical, emotional, intellectual and social growth and development needs to be paid attention to. Sometimes there are people who easily judge other people and make comments. The purpose of writing this article is to analyze various life problems experienced by humans from toddler to late adulthood and how developmental psychology views these problems. This research uses descriptive qualitative methods with interview and observation techniques as well as literature study by searching for various references from various literature, analyzing theories, comparing with field facts and drawing conclusions. The implication of this research is the importance of problem analysis before expressing an opinion based on a developmental psychology view.